Philosophy of Education as the Foundation for Building an Anti-Corruption Culture in Schools: The Perspektive of Plato, Ki Hajar Dewantara, and John Dewey - Raharjo; Muhammad Ilham Halwani (Social Journal of Studies in Education, 2025)
Corruption is a serious problem that is rooted in various sectors of life, including the world of education. This study aims to analyze how educational philosophy can be used as a foundation in forming an anti-corruption culture in schools. This study uses a qualitative approach with a literature study method to analyze philosophical concepts and their application in anti-corruption education. The findings of the study show that the philosophy of Islamic education contains values such as honesty, responsibility, justice, and integrity that are relevant in building the character of students. The thoughts of figures such as Plato, Ki Hajar Dewantara, and John Dewey also contributed to the understanding of the importance of character education in preventing corruption. The implementation of these values can be done through integration in the curriculum, teacher examples, transparent school policies, and cooperation with families and communities. By applying the philosophy of education as the basis for forming anti-corruption awareness and attitudes, schools can be at the forefront of producing a generation with integrity and commitment to building a society that is clean from corruption.